Shorefall : a novel - Bennett, Robert Jackson, 1984- (Bennett, Robert Jackson, 1984- Founders trilogy, 2020)
"Having narrowly saved the metropolis of Tevanne from destruction, Sancia Grado and her allies have turned to their next task: sowing the seeds of a full-on magical-industrial revolution. If they succeed, the secrets behind scriving--the art of imbuing everyday objects with sentience--will be accessible to all of Tevanne's citizens, much to the displeasure of the robber-barons who've hoarded this knowledge for themselves. But one of Sancia's enemies has embarked on a desperate gambit, an attempt to resurrect a figure straight out of legend--an immortal being known as a heirophant. Long ago, the heirophant was an ordinary man, but he's used scriving to transform himself into something closer to a god. Once awakened, he'll stop at nothing to remake the world in his horrifying image. And if Sancia can't stop this ancient power from returning? Well, the only way to fight a god...is with another god"--